PENGARUH KEPEMIMPINAN DAN MOTIVASI TERHADAP KINERJA PEGAWAI DENGAN LINGKUNGAN KERJA SEBAGAI VARIBAEL MODERATING PADA PEGAWAI PT. BANK PEMBANGUNAN DAERAH JAWA TIMUR Tbk. CABANG SITUBONDO - Safitri, Intan Nuriyana; Arief, Mohammad Yahya; Anshory, Muhammad Iqbal (Fakultas Ekonomi dan Bisnis, 2024)
The purpose of the study was to determine the Influence of Leadership and Motivation on Employee Performance with the Work Environment as a Moderating Variable on Employees of PT. Bank Pembangunan Daerah Jawa Timur Tbk. Situbondo Branch. The sampling technique used in this study was the Total Sampling method or saturated samples of 40 people. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM) The results of the study showed that Leadership had a negative but significant effect on Employee Performance, Motivation had a positive and significant effect on Employee Performance, Work Environment could not moderate the influence of Leadership on Employee Performance, Work Environment significantly became a moderating variable for the influence of motivation on Employee Performance.